LANGUAGE STYLES OF JOKO WIDODO’S SPEECH IN CHATTING ON YOUTUBE CHANNELS - Ni Made Saraswati Ansari; Ni Nyoman Padmadewi (Lingua Scientia, 2022)
This research analyzed the language style of Joko Widodo's speech in chatting with the hosts of three YouTube channels. The videos were published on January 18, March 17, and April 16, 2019. The writer applied two theories in analyzing the speech: S.P.E.A.K.I.N.G theory from Dell Hymes (1974) and Martin Joos' theory (1976) about language styles. S.P.E.A.K.I.N.G is derived from the situation, participants, ends, act, key, instrumentality, norms, and genre. While language styles are divided into five, those are frozen or oratorical, formal or deliberative, consultative, casual, and intimate styles. This study is qualitative descriptive research. In analyzing the data, the writer did it by watching those videos, transcribing President Joko Widodo's speech, classifying the data or speech based on the language styles, narrating the data, and the last step was interpreting. Through the analysis, the writer finds that the most prominent style used by Joko Widodo is the casual style.